CONTROL BEHAVIORS AFFECTING INVESTORS INVESTMENT DECISION MAKING (STUDIES ON STUDENTS AT HIGHER EDUCATION SOUTH KALIMANTAN) - Ainun Logitama; Lilik Setiawan; Atma Hayat (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Investors have strong reasons for making investment decisions, namely hoping to provide returns that are more than what they have invested. The investment decision is in the form of a decision to buy, sell, or maintain ownership of its shares. There are five factors that can influence investors in making investment decisions, including heuristics, risk aversion, financial tools, and firm-level corporate governance, and financial leteracy. This study aims to determine whether these five factors influence investor behavior in making investment decisions. The survey was conducted on 100 active student respondents in South Kalimantan Higher Education. Primary data obtained through distributed questionnaires and then analyzed descriptively. The results of the study show that investors really consider these five factors in making investment decisions. Keywords: investor behavior, investment decision making